Assessment literacy and practices of Literature-in-English teachers in Nigeria - Eucharia Okwudilichukwu Ugwu; Francis Ezeokoli (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2022)
The study investigated Literature-in-English teachers' assessment literacy and practices in Nigeria. The mixed method design was adopted, and the participants were 47 secondary school teachers selected from 47 schools in the Ibadan metropolis, Oyo, State, Nigeria. Teachers' Assessment Literacy Test (r=.78), Class Assessment Checklist, and Interview Guide were used to collect quantitative and qualitative data. The quantitative data were analyzed using the descriptive statistics, and the qualitative data were content analyzed. Analysis of data exposed teachers' inadequate knowledge of assessment and total neglect of assessment in their teaching-learning process. The frequency of teachers' practice of assessment was very low. Only 2% of the lessons taught within 10 weeks were guided with adequate formative or summative assessment; and 82% of the lessons were delivered with no assessment. Teachers used very few and easy methods of assessment that may not serve improvement purposes. They also have misconceptions about assessment. The results have implications for effective Literature-in-English pedagogy